2021
DOI: 10.5144/0256-4947.2021.51
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic dental injuries in special health care needs children and association with obesity

Abstract: BACKGROUND: Special needs children are at a higher risk of dental trauma because of neurological, physical, mental, and behavioral impairments. They are also at higher risk of developing obesity due to the side effects of medication. OBJECTIVE: Assess the association between traumatic dental injuries (TDIs) and obesity in children with special health care needs. DESIGN: Analytical cross-sectional study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(58 citation statements)
references
References 27 publications
(15 reference statements)
5
53
0
Order By: Relevance
“…Of these, 15 articles were excluded and are listed in Supplementary Table S1 , along with the reasons for their exclusion ( Supplementary Table S1 ). Therefore, 38 studies were included in this review [ 10 , 11 , 12 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. No additional studies were found upon hand searching or searching the gray literature.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 15 articles were excluded and are listed in Supplementary Table S1 , along with the reasons for their exclusion ( Supplementary Table S1 ). Therefore, 38 studies were included in this review [ 10 , 11 , 12 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. No additional studies were found upon hand searching or searching the gray literature.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…Thirty-five studies were cross-sectional [ 10 , 11 , 12 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 46 , 47 , 48 , 50 , 51 ], one was a longitudinal study [ 45 ], and two were retrospective studies [ 28 , 49 ]. Twenty-two studies were conducted in or near Riyadh [ 10 , 11 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 32 , 33 , 34 , 35 , 38 ...…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations